Ontological anthropology and the deferral of critique - BESSIRE, LUCAS; BOND, DAVID (American ethnologist, 2014)
What does ontological anthropology promise, what does it presume, and how does it contribute to the formatting of life in our present? Drawing from our respective fieldwork on how Indigenous alterity is coenvisioned and how the lively materiality of hydrocarbons is recognized, we develop an ethnographic and theoretical critique of ontological anthropology. This essay, then, provides an empirical counterweight to what the ontological turn celebrates of Native worlds and what it rejects of modernity. In it, we examine the methodological and conceptual investments of ontological anthropology. The figure of the ontological as commonly invoked, we argue, often narrows the areas of legitimate concern and widens the scope of acceptable disregard within social research. We chart how this paradigm's analytical focus on the future redefines the coordinates of the political as well as anthropology's relation to critique. Finally, we formulate three conceptual theses that encapsulate our criticism and open this discussion to further debate.